GSE4‐loaded nanoparticles a potential therapy for lung fibrosis that enhances pneumocyte growth, reduces apoptosis and DNA damage. Issue 3 (27th February 2021) - Pintado‐Berninches, Laura; Montes‐Worboys, Ana; Manguan‐García, Cristina; Arias‐Salgado, Elena G.; Serrano, Adela; Fernandez‐Varas, Beatriz; Guerrero‐López, Rosa; Iarriccio, Laura; Planas, Lurdes; Guenechea, Guillermo; Egusquiaguirre, Susana P.; Hernandez, Rosa M.; et al.
Abstract: Idiopathic pulmonary fibrosis is a lethal lung fibrotic disease, associated with aging with a mean survival of 2‐5 years and no curative treatment. The GSE4 peptide is able to rescue cells from senescence, DNA and oxidative damage, inflammation, and induces telomerase activity. Here, we investigated the protective effect of GSE4 expression in vitro in rat alveolar epithelial cells (AECs), and in vivo in a bleomycin model of lung fibrosis. Bleomycin‐injured rat AECs, expressing GSE4 or treated with GSE4‐PLGA/PEI nanoparticles showed an increase of telomerase activity, decreased DNA damage, and decreased expression of IL6 and cleaved‐caspase 3. In addition, these cells showed an inhibition in expression of fibrotic markers induced by TGF‐β such as collagen‐I and III among others. Furthermore, treatment with GSE4‐PLGA/PEI nanoparticles in a rat model of bleomycin‐induced fibrosis, increased telomerase activity and decreased DNA damage in proSP‐C cells. Both in preventive and therapeutic protocols GSE4‐PLGA/PEI nanoparticles prevented and attenuated lung damage monitored by SPECT‐CT and inhibited collagen deposition. Lungs of rats treated with bleomycin and GSE4‐PLGA/PEI nanoparticles showed reduced expression of α‐SMA and pro‐inflammatory cytokines, increased number of pro‐SPC‐multicellular structures and increased DNA synthesis in proSP‐C cells, indicating therapeutic efficacy of GSE4‐nanoparticles in experimental lung fibrosis and a possible curative treatment for lung fibrotic patients.